2019
DOI: 10.1002/cncr.31941
|View full text |Cite
|
Sign up to set email alerts
|

Impact of conditioning intensity on outcomes of haploidentical stem cell transplantation for patients with acute myeloid leukemia 45 years of age and over

Abstract: Background T cell–replete haploidentical stem cell transplantation (haplo‐SCT) is a valid therapeutic option for adult patients with high‐risk acute myeloid leukemia (AML) lacking an HLA‐matched sibling or unrelated donor. Method We retrospectively analyzed the outcomes of 912 AML patients ≥45 years of age who had undergone haplo‐SCT with either myeloablative conditioning (MAC; n = 373) or reduced intensity conditioning (RIC; n = 539) regimens. Results The median follow‐up was 31.1 and 25.7 months for MAC and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 42 publications
0
10
0
1
Order By: Relevance
“…Older age historically has been considered a relative contraindication for haplo-SCT, as physicians are often concerned about high TRM in the setting of MAC (18,19). To address this problem, various reduced-intensity conditioning regimens have emerged.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Older age historically has been considered a relative contraindication for haplo-SCT, as physicians are often concerned about high TRM in the setting of MAC (18,19). To address this problem, various reduced-intensity conditioning regimens have emerged.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of RIC on TRM in the haplo-SCT setting from retrospective studies is conflicting (18,36,37). Although some studies have demonstrated the decreased TRM and reduced toxicity of RIC in older patients or patients with comorbidities, it is also controversial that whether decreased TRM will further translate into improved survival when comparing RIC and MAC regimens.…”
Section: Discussionmentioning
confidence: 99%
“…After stratifying patients into younger and elder groups, we tested the prognostic ability of methylation subtypes in the two groups with different ages. The result showed that although elder patients had worse survival rate than younger patients, [19][20][21] those samples classified into subtype 1 still had better prognosis than subtypes 2 and 3. Combining patient age and methylation subtypes, we found out a better classification for AML samples.…”
Section: Discussionmentioning
confidence: 96%
“…The result showed that elder patients had worse prognosis than younger patients, this was reasonable and consistent with the results of previous studies. [19][20][21] Expected for the survival rate and clinical behaviors, we also compared the somatic mutations between the three subtypes. As a result, we found that patients in subtype 3 were with more frequent FLT3 mutations compared with subtypes 1 and 2 (P = 2.207e-02, 1.075e-04 respectively, Figure 2C).…”
Section: Samples In Subtype 1 Were With Better Prognosis Compared Wmentioning
confidence: 99%
“…A nivel global se ha ido incrementando la edad límite para realizar los trasplantes ya que esta enfermedad es habitual en adultos mayores. Así, se ha descrito que la aplicación racional en el ajuste en la intensidad del tratamiento, permite realizar el trasplante en pacientes cada vez más mayores con resultados similares, fundamentado esto en la asignación selectiva del tipo de acondicionamiento para el trasplante según el performance status y una minuciosa evaluación pre trasplante por sistemas cardiopulmonar, hepático, renal, digestivo, etc 12 . Recientemente, la sociedad Europea de trasplante de médula ósea realizó un análisis de 713 pacientes mayores de 70 años comparados con 16.000 pacientes entre 50 y 69 años trasplantados por LMA entre 2001 y 2014.…”
Section: Discussionunclassified